On the limits of punishment in the peripheral Argentina. The prison of Neuquén (1904-1945) (Quinto Sol, 2013)
In this article, we offer a contribution to the social history of punishment, attending to a historical approach upon the patagonic prison of Neuquén (U.P 9). The main topics are both the inmates´ material life and the penitentiary policies displayed in this prison, with the purpose of showing the differents ways in which the small local prison´s bureaucracies interpreted and executed  national regulations. Social features of the inmates are sketched, focusing specially upon the differences between common and political prisoners. This paper tries to discuss the supposed depth, coherence and regularity that literatura usually atributed to the Argentine´s positivist, late nineteenth Century penitentiary´s reforms. Neuquén´s prison is compared with the much bigger and well-provided Ushuaia´s prison, settled in the southern areas of Argentina.
Keywords: Prison; Patagonia; justice; State